'Being Affluent, One Drinks Wine’::Wine counterfeiting in mainland China - Shen, Anqi (International Journal for Crime, Justice and Social Democracy, 2018)
This article focuses on wine counterfeiting and the policing of fake wines in mainland China. Relying on rich data drawn from published materials and open sources, it discusses three important themes in relation to product counterfeiting: the definitional issue; the scope, scale and organisation of the counterfeiting business; and law enforcement against product piracy. The aim is to broaden our knowledge about the counterfeiting trade, to develop a clear understanding of the illegitimate market, and to help to renew countermeasures that not only enable the exercising of tighter control over the counterfeiting industry but also disrupt the illegal behaviours of counterfeiters. Rather than place emphasis on the protection of intellectual property rights, this article stresses public health concerns with regard to dangerous counterfeit goods such as fake wines. Examining wine counterfeiting within the existing analytical framework of organised crime research, this article contributes to analysis of the nature of product counterfeiting and the issue of policing counterfeit goods